Functional Significance of Facilitation Between the Pronator Teres and Extensor Carpi Radialis in Humans: Studies with Electromyography and Electrical Neuromuscular Stimulation - Naito, Akira; Fujii, Hiromi; Sato, Toshiaki; Suzuki, Katsuhiko; Nakano, Haruki (IntechOpen, 2012)
None